ANALYSIS OF FACTORS CAUSING SUICIDE IN PRISONERS IN MADIUN CLASS I PRISON - Irfansyah, Ahsyamsa Naufal; Simanjuntak, Meitisa Vanya (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The study aims to analyze the influence of various factors on the mental condition of prisoners and to provide recommendations for reducing the risk of suicide. This research employs a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation, involving informants from the Class I Madiun Correctional Facility, including staff and prisoners. Data analysis was conducted using qualitative analysis techniques based on the Miles and Huberman model. The findings indicate that prisoners go through five stages of suicide: suicidal ideation, suicidal intent, suicidal threat, suicidal gesture, and suicidal attempt. Identified contributing factors include perceptions of punishment, feelings of injustice, lack of support, and unfavorable conditions within the correctional facility. Challenges in the implementation of rehabilitation programs and psychological health services were also identified, affecting the mental well-being of prisoners. Keywords: Factor; Suicide; Correctional Institutions